The Effect of Project-Based Stem Education Approach on Academic Achievement and Stem Career Interests in Science - Tanır, Halil; Türkmen, Lütfullah (South Eastern European Journal of Public Health, 2024)
The aim of this study is to determine the effect of the project-based STEM learning method prepared in accordance with the Science and Technology course curriculum on academic achievement and STEM Career Interest levels. Pre-test post-test control group experimental design was used in the study. In this context, the sample of the study consisted of 52 (n=26 experimental and n=27 control) volunteer 6th grade students studying in two different branches at Karatay Secondary School in Karatay district of Konya province in the second semester of 2021-2022 academic year. A placement test was administered in order to determine the branches in which the study would be conducted. According to the results of the exam, volunteer students studying in the closest level branches were included in the study. The students in the experimental group were taught according to the project-based STEM learning method prepared according to the outcomes of the Support and Motion System, Force and Motion, Sound Insulation, Thermal Insulation units for 64 lesson hours. The students in the control group were taught the above-mentioned units by the same instructor according to the existing program for 64 class hours. Both experimental and control group students were administered the skills-based academic achievement and STEM Career Interest Scale prepared by the Ministry of National Education as pre-test and post-test. The data obtained from the pre-test and post-test applications were evaluated in SPSS 26.0 package program. In the statistical analysis, it was found that there was a statistically significant difference between the students in the experimental and control groups in favor of the students in the experimental group (p<0.05). According to the findings obtained from the statistical analysis, it was concluded that the project-based STEM teaching method in science education increased the level of academic achievement and interest in STEM professions. Based on this result, it is predicted that students' academic achievement levels can increase with the more frequent use of project-based STEM learning method in science education by teachers